Hryhorii Skovoroda and the Present - Марчук, К. (Київський національний університет імені Тараса Шевченка, 2022)
The article is devoted to the study of the epistolary heritage of Hryhorii Skovoroda. Particular attention is paid to the theme of redundancy, affinity and friendship. Other views and philosophical foundations of the thinker are generally outlined. It is proved that the thoughts of the great philosopher do not lose their importance in modern times.

Досліджено епістолярну спадщину Григорія Сковороди. Особливу увагу приділено темі надмірності, сродності та дружбі. Загально окреслено інші погляди та філософські засади мислителя. Доведено, що думки великого філософа залишаються актуальними й донині.
Григорій Сковорода і сучасність
Keywords: Григорій Сковорода; український філософ; епістолярна спадщина; сродність; надмірність; дружба; Hryhorii Skovoroda; Ukrainian philosopher; epistolary heritage; kinship; redundancy; friendship